Kinematic and Dynamic Analysis of the Partially Decoupled Parallel Manipulator - Canguo Zhang; Xiaoyu Ni; Zhanfeng Song; Yongjie Zheng (Jixie chuandong)
Aiming at the machining of complex curved surface parts with parallel machine tools， a novel partially decoupled parallel manipulator （PM） is proposed. The degree of freedom and the decoupling performance of the mechanism are analyzed. The formula for the kinematic relationship between the driving branches and the moving platform is deduced by the vector method. The motion of each component in the parallel manipulator is analyzed. Considering the gravity， inertia force and moment of inertia of the components in the mechanism， a dynamic model of the parallel manipulator is established. The kinematic and dynamic equation of the PM is verified based on advanced CAD software. The singularity of the PM is analyzed， which provides theoretical and technical foundations for its application.